Mapping the Global Multimedia Value Chain of Assassin’s Creed: Shadows (2021–2025) - Akbar, Ahmad Taufik; Adrian, Stefan Risky; Sirhadi, Dharma; Purbantina, Adiasri Putri (Global Economic, Social, and Development Review, 2026)
The global digital game industry has experienced rapid growth, accompanied by increasing complexity in production processes, particularly the development of Triple A (AAA) games involving multinational collaboration and large scale creative labor. This study aims to analyze and map the Global Multimedia Value Chain (GMVC) of Assassin’s Creed: Shadows (2021–2025) development using the Creative Value Chain framework. Employing qualitative case study approach, this research draws on secondary data sources, including official Ubisoft documentation, developer credits, industry reports, media interviews, and relevant academic literature. The findings revealed, the production of Assassin’s Creed: Shadows represents highly fragmented yet integrated global production network, involving more than fifteen Ubisoft studios across North America, Europe, and Asia. Ubisoft Québec functions as the central governance hub, coordinating creative direction, technological development, and project management. Each studio contributes specialized value based on geographical expertise, such as historical research, engine optimization, audio visual design, quality assurance, and global marketing strategies. In addition, the Support Functions, including education and training, archiving and preservation, management and regulation, as well as sustainability and social responsibility, play a critical role in ensuring long term value creation, cultural authenticity, intellectual property protection, and environmental accountability. This study demonstrates the success of Assassin’s Creed: Shadows through the technological innovation, financial investment, and effective orchestration of a global multimedia value chain. The research contributes to the literature on creative industries by highlighting how AAA game production operates as an interconnected economic, cultural, and technological ecosystem on a global scale.